The effect of age and maturation on anthropometric characteristics and physical abilities of youth South African footballers - De Beer, Ashley (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Currently there is limited research investigating the football related abilities of youth South African individuals. Populations from North and South America, Europe and Asia have been extensively covered in terms of their anthropometric characteristics, physical abilities, technical competency, tactical understanding as well as various personality traits. In describing these details, and especially how each is affected during the ageing and pubertal process, a more informed understanding of the talent development systems is created. A holistic approach to talent development is required to effectively and efficiently produce elite level footballers. An important consideration is the unique socio-economic environment many youth footballers experience which may impact on the talent development process. The present study therefore sought to quantify the anthropometric characteristics and the physical ability level of youth South African footballers from Local Football Association in Makhanda in the Sarah Baartman Region of the Eastern Cape province. In order to achieve this a two-factorial design was used with age and maturity status as independent variables. Anthropometric characteristics were tested by finding the height, weight, body mass index and total fat percentage of participants. Physical ability was determined by results for aerobic capacity, power, acceleration, speed and agility. All tests were football specific and had been widely used in a variety of footballing studies. Additional demographic and socio-economic information was also recorded. A total of 136 participants were placed in their respective Under 11, 13, 15 or Under 19 age groups, while the maturity status of 96 participants were stratified into five distinct categories. Statistical analyses was conducted using p-value significance, with appropriate Tukey post-hoc tests administered when necessary, while effect sizes were calculated using Cohen's d. Significant changes and practical effect sizes were present for nearly all dependent variables when either stratified by age or by maturity. Total fat percentage was the only dependent variable which was not influenced by either age or maturity. Age and maturity effect sizes for total body fat percentage indicated practical changes present which did not occur during statistical analysis. The present results indicate poor values when compared to normative data or that of other football playing study populations. Further longitudinal research is required to better understand individual growth rates for youth South African footballers, particularly from the Makana region. Implications of the thesis may determine long term development pathways, while the delayed maturity rate is a critical finding which needs to be further researched.
Keywords: Soccer -- Physiologial aspects; Soccer players -- South Africa -- Makhanda -- Physiology; Soccer players -- South Africa -- Makhanda -- Psychophysiology; Makana Local Football Association (South Africa)